Fear of getting Covid-19: A challenge to elective surgical practice and ways to overcome - Hafiz Muhammad Ijaz ul Haq, Hafiz Muhammad Ijaz ul Haq; Fawad Aamir Mirza, Fawad Aamir Mirza; Rizwan Aziz, Rizwan Aziz; Ahmad Raza, Ahmad Raza; Muhammad Hanif, Muhammad Hanif; Sohaib Haider, Sohaib Haider (Journal of Rawalpindi Medical College, 2022)
Background: Covid-19, a global pandemic has a huge impact on surgical practice. There is transmission risk of Covid-19 during the elective surgery and nowadays it is a part of informed consent process. This has an impact on patient decision making as it creates anxiety and fear. Objective: To evaluate patient experience (fear of getting Covid-19) from elective surgery and challenges of elective surgical practice and ways to overcome during this pandemic era. Methods: This study was an observational cross-sectional survey and it has been conducted in General Surgery Department of Dr Akbar Niazi Teaching Hospital, Islamabad, from May to August 2021 after approval of Institutional Review Board (IRB). Participants for elective surgery and their negative report of Covid-19 infection by polymerase chain reaction (PCR) were included in the study. Fear of Covid-19 infection was measured through “fear of Covid-19 scale” by Ahorsu et al and analyzed. All findings were entered in a structured Proforma. Data was entered in SPSS version 26 and analyzed. Effect modifier chi square was used to find out the patient’s dropout due to getting Covid-19 infection from surgery. Results: Total 200 patients were included; 62% patients were male and 38% were females. The mean age of the patients was 38.64±12.08 years. The statistical analysis showed that there was a very significant association between FCV-19 scale and getting Covid-19 infection from elective surgeries (p ≤ 0.05). When stratified FCV-19 scale with education status of all patients there was a very significant association between them (p=0.001). The patient’s observations regarding FCV-19 questionnaire, most of the patients were disagreed (46.3%) to getting Covid-19 infection from their elective surgeries or any fear of Covid-19 infection. The actual dropout of patients from elective surgery due to fear of getting Covid-19 infection during surgery or staying in hospital was 7.5%. Conclusion: Fear of getting Covid-19 is still present in some of the patients who visit hospitals for elective surgeries. Discussing the various steps taken by the institute to improve patient safety and minimize risk of Covid-19, greatly enhanced their confidence in elective surgery and improved satisfaction level. Key words: Covid-19; Fear; Fear of Covid-19 Scale; Elective Surgical Procedures.